Temporal decoupling of oxy- and deoxy-hemoglobin hemodynamic responses detected by functional near-infrared spectroscopy (fNIRS) - Tam, Nicoladie D; Zouridakis, George (British Journal of Healthcare and Medical Research, 2014)
This study provides experimental evidence that there is temporal decoupling between the hemodynamic responses of oxy- and deoxy-hemoglobin (Hb) as detected by functional near-infrared spectroscopy (fNIRS). Using 64 spatially distributed optrodes to record motor cortical activities during a free arm movement task (right-left and front-back movements), we detected that the temporal profile of oxy- and deoxy-Hb responses are desynchronized and decoupled (i.e., oxy- and deoxy-Hb levels do not rise and fall at the same time). We correlated four different measures of hemodynamic profiles with the arm movements, namely, oxy- (HbO2) and deoxy-hemoglobin (Hb) and their summation (HbO2 + Hb) and difference (HbO2 - Hb) signals. These measures correspond to the changes in oxygen delivery, oxygen extraction, total blood volume delivered, and total oxygenation with specific movement directions, respectively. They revealed different components of the hemodynamic response in a localized neuronal population in the motor cortex. The results suggested that, by using these four measures, oxygen delivery and oxygen extraction can be coupled in one movement direction, but decoupled in another movement direction for the same human subject executing the same movement task. Oxygen delivery and oxygen extraction do not always co-vary together temporally. Thus, using a single measure of oxygen delivery or extraction alone may not be sufficient to determine whether the cortical area is activated or deactivated. Rather, a combination of all four measures of hemodynamic signals that represent temporal coupling and decoupling of oxygen delivery and extraction is needed to differentiate the temporal profiles of neural activation and deactivation. It demonstrated that different hemodynamic measures can reveal temporally decoupled activation/deactivation patterns differentially during the right-left and front-back motor task. Therefore, relying on a single measure of deoxy-Hb may be insufficient to characterize the neural responses without the oxy-Hb measure. Orthogonal arm movement (right-left vs. front-back) directions can be differentiated based on the differential temporally coupled and decoupled hemodynamics.